The Evolution of Predator Resemblance in Avian Brood Parasites - York, Jennifer E. (Frontiers in Ecology and Evolution, 2021)
Predators have profound effects on prey behaviour and some adult brood parasites exploit the antipredator defences of their hosts via predator resemblance. Clarifying host perception of such stimuli is important for understanding the adaptive significance of adult brood parasite characteristics, and the mechanisms by which they misdirect hosts. Here I review the literature to summarise whether predator resemblance is adaptive, and natural variation in host responses to these stimuli. I also provide a framework for the information ecology of predator resemblance, which is based on the principles of signal detection theory and draws from empirical evidence from the common cuckoo, Cuculus canorus, as the most widely studied system. In this species, visual and acoustic hawk-like stimuli are effective in manipulating host defences. Overall, contrasts across host responses suggest that different modalities of information can have independent effects on hosts, and that predator resemblance takes advantage of multiple sensory and cognitive processes. Host perception of these stimuli, the degree to which they are processed in an integrated manner, and the physiological processes underlying regulation of responses, now present exciting §avenues for brood parasitism research.